Vitamin D receptor genotype influences risk of upper respiratory infection. Issue 8 (22nd August 2018) - Jolliffe, David A.; Greiller, Claire L.; Mein, Charles A.; Hoti, Mimoza; Bakhsoliani, Eteri; Telcian, Aurica G.; Simpson, Angela; Barnes, Neil C.; Curtin, John A.; Custovic, Adnan; Johnston, Sebastian L.; Griffiths, Christopher J.; et al.
Abstract: SNP in the vitamin D receptor ( VDR ) gene is associated with risk of lower respiratory infections. The influence of genetic variation in the vitamin D pathway resulting in susceptibility to upper respiratory infections (URI) has not been investigated. We evaluated the influence of thirty-three SNP in eleven vitamin D pathway genes ( DBP, DHCR7, RXRA, CYP2R1, CYP27B1, CYP24A1, CYP3A4, CYP27A1, LRP2, CUBN and VDR) resulting in URI risk in 725 adults in London, UK, using an additive model with adjustment for potential confounders and correction for multiple comparisons. Significant associations in this cohort were investigated in a validation cohort of 737 children in Manchester, UK. In all, three SNP in VDR (rs4334089, rs11568820 and rs7970314) and one SNP in CYP3A4 (rs2740574) were associated with risk of URI in the discovery cohort after adjusting for potential confounders and correcting for multiple comparisons (adjusted incidence rate ratio per additional minor allele ≥1·15, P for trend ≤0·030). This association was replicated for rs4334089 in the validation cohort ( P for trend =0·048) but not for rs11568820, rs7970314 or rs2740574. Carriage of the minor allele of the rs4334089 SNP in VDR was associated with increased susceptibility to URI in children and adult cohorts in the United Kingdom.